The role of chaperones and Sec machinery in protein secretion - Ito, Koreaki (Henry Stewart Talks, 2007)
Importance of protein translocation, Identification of Sec factors, Structure and function of translocon, an evolutionarily conserved membrane protein complex that serves as a polypeptide-conducting channel, Structure and function of SecA, a translocation-driving ATPase, Unique regulation of SecA by SecM, a protein that interacts with the ribosomal exit tunnel